Conductive graphene coated carboxymethyl cellulose hybrid fibers with polymeric ionic liquids as intermediate. (15th March 2022) - Wang, Jingjing; Liang, Yuan; Huang, Shuohan; Jin, Wenbin; Li, Zefeng; Zhang, Zhenfei; Ye, Chunlin; Chen, Yuwei; Wei, Peng; Wang, Yanping; Xia, Yumin
Abstract: In this study, a kind of polymeric ionic liquid (PIL) called PIL-Cl was synthesized and modified to obtain conductive graphene coated carboxymethyl cellulose hybrid fibers. Carboxymethyl cellulose (CMC) was formed into fibers by wet spinning assisted with PILCl. Co-precipitation test of CMC and PIL-Cl demonstrated that PIL-Cl could precipitate with CMC through strong electrostatic interaction and molar ratio of CMC and PIL-Cl (calculated in repeating units) would affect the formation of precipitation. Secondly, modified PIL-Cl named PIL-Ac was used as an intermediate connecting CMC fiber and graphene to fabricate conductive CMC/PIL/graphene fibers. A series of tests were performed on CMC/PIL/graphene fibers, including Raman spectroscopy, scanning electron microscopy and conductivity test. The results showed that PIL-Cl could help form CMC fiber, and PIL-Ac could functionalize it and make it conductive.